Development of an embedded coolant system incorporat-ing minimum quantity lubrication for CNC milling applications - Hendrawan, Yogi Muldani; Pratama, Andri; Ihsyani, Taufik Abdul Karim; Ruswandi, Ruswandi; Harja, Herman Budi (Politeknik Negeri Lhokseumawe, 2025)
Machinery applications often generate excessive heat due to friction between cutting tools and work-piece materials. To mitigate heat and friction, the use of coolant is necessary in machining operations. Wet coolant systems risk environmental and health concerns because of their consumption rates and chemical content whose waste requires recycling, a process that consumes additional energy and contributes to increased carbon emissions. As a sustainable alternative, the Minimum Quantity Lubrication (MQL) method supplies a fine mist of lubricant in minimal volumes, thereby reducing waste while enhancing machining performance. This study aims to develop an Embedded Coolant System (ECS) based on the MQL method for CNC milling machines, ensuring both ease of integration and effective cooling performance. The ECS was designed with a simplified open-loop controller using an Arduino Mega 2560, a peristaltic pump, and air-pressure control to regulate the coolant mist. Initial calibration was conducted to establish the coolant flow-rate equation as a function of motor speed. Experimental validation was carried out using aluminum and ST-37 steel with HSS and carbide tools, comparing conventional air-pressure cooling (APC) and the proposed MQL-ECS. The results demonstrate that the MQL-ECS significantly reduces machining temperatures and improves surface roughness compared with APC. For aluminum, the average temperature decreased by up to 3% from 30.3 oC, while surface roughness improved by 31% from 1.1µm. For ST-37, the temperature decreased by 5.5% from 31.1 oC, and surface roughness improved by 72.74% from 5.96 µm. These findings confirm both the effectiveness and environmental benefits of the proposed system, providing a feasible solution for modern CNC operations.